Penerapan Terapi Murotal Al-Qur’an untuk Menurunkan Kecemasan pada Pasien Pre Operasi Di RSU Aro Pekalongan - Nur Pratiwi; Maulidta Karunianingtyas (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aimed to evaluate the effectiveness of murottal Al-Qur’an therapy in reducing anxiety levels among preoperative patients at RSU Aro Pekalongan. A quantitative empirical design using a one group pretest–posttest approach was applied to assess intra-subject changes before and after intervention. The sample consisted of four respondents selected through purposive sampling based on specific inclusion criteria. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS), which has demonstrated high reliability in clinical assessment. The intervention involved listening to Surah Ar-Rahman for approximately 15 minutes prior to surgery. The findings indicated a consistent decrease in anxiety scores across all participants, with varying degrees of reduction reflecting individual responses to the therapy. These results suggest that murottal therapy provides both physiological and psychological benefits, contributing to improved emotional stability and relaxation. The study highlights the potential of integrating spiritual-based interventions into nursing practice as a complementary approach to enhance preoperative care and patient well-being.